Sistem Informasi Pengendali Rincian Obyek Belanja Operasional Di Biro Hukum Kantor Gubernur Kalimantan Barat - Dini Aljuniarti Putri; Rabiatul Adwiya; Latifah Latifah (Jurnal Sistem Informasi Akuntansi, 2021)
with developments in the world of work and technology that require fast-paced. Currently, the Legal Bureau of the West Kalimantan Governor's Office is doing manual recording with Ms. Excel mediaso that it is prone to errors and takes a long time so it is hoped that the existence of this Shopping Object Details Controlling Information System can simplify the detailing process to the maximum and shorten the checking time. A computerized system is the best solution to solve the problems that exist in this Legal Bureau, and it is hoped that with a computerized system, an activity that is more effective and efficient can be achieved in supporting the activities of this Legal Bureau. The resulting system divides level access rights into 2 users, namely access rights at the level of the Chair of the Finance Subdivision and access rights at the Treasurer level of the Finance Subdivision. Where each access level has its own limitations on the applications made. The finance subdivision treasurer can view the final report on operational expenditure expenditures, manage users, manage operational expenditure transactions, manage types of operational expenditure transactions, login and logout. Meanwhile, the head of the finance sub-section can only log in and see the results of the spending control report and logout